Innovation and equality: an approach to constructing a community governed network commons. Issue 1 (2nd January 2022) - Foley, Rider W.; Sylvain, Olivier; Foster, Sheila
ABSTRACT: Networked computing affords users distinct opportunities to communicate with each other, build relationships, transact business, and create. Yet, the digital divide perpetuates existing disparities between social groups. Interventions that rely on private ownership or philanthropy often fall short. Efforts to redress these disparities require collaboration across academic disciplines and with government and private sector organizations. This paper chronicles efforts in Harlem to address this through a collaborative approach to networked computing. We draw on two concepts–responsible innovation and co-governance–to sketch a community-based approach to networked computing. Second, the article identifies two potential systems, based in property law, through which a cross-section of community stakeholders could govern this networked computing infrastructure. In the end, this article seeks to integrate aspects of co-design and responsible innovation and reflects upon building bridges between researchers across academic disciplines, as well as the opportunities and difficulties of partnering with entrepreneurs and civic leaders.